The Hypoxic Preconditioning Effect On Senescence Cell Process In Cultured Adipose-Derived Mesenchymal Stem Cells (AMSCs) - Nadiar Dwi Nuarisa; I Gde Rurus Suryawan; Andrianto Andrianto (Jurnal Kardiologi Indonesia, 2018)
Introduction : Stem cell therapy for myocardial regeneration is expected to increase cardiomyocyte proliferation and trigger neovascularization to improve cardiomyocytes. Mesenchymal Stem Cells (MSCs) are ideal candidates for regenerative medicine and immunotherapy. But low viability of MSCs is a major challenge in this alternative therapy. Therefore, a cytoprotective strategy is needed, one of them is hypoxic preconditioning which can significantly increase survival stem cells after being transplanted. MSCs are known to have a limited life span, after experiencing several splits MSC will enter the senescence process. It is known that hypoxia can also increase cell proliferation and differentiation potential in vitro and in vivo through the role of Octamer-4 (Oct-4) as a regulator of the pluripotency gene. Methods : Experimental laboratory studies (in vitro studies) using human-AMSCs which were given hypoxic preconditioning, observed as a immunocytochemistry. Results : The results showed that hypoxic precondition (1% O2) inhibited the senescence process. It can be seen in the lower expression of senescence in hypoxic conditions at P6, P7, P8, P9, P10 compared to normoxic ((p=0,004, p=0,001, p=0,009, p=0,013, p=0,024. There is a significant difference in the senescence expression of each passage in hypoxic and normoxic conditions with the highest expression at P10. In addition, we also observed AMSCs differentiation through the Oct-4 expression. It is showed that Oct-4 expression were higher in hypoxia compared to normoxia on P7, P8, P9, P10 (p=0,009, p=0,009, p=0,030, p=0,0001). Conclusions : Hypoxic preconditioning have the effect of inhibiting the senescence process on Adipose-derived MSCs (AMSCs) or prolonging their life span. The longer life span of AMSCs is also seen by higher cell differentiation potential from increased expression of Oct-4. However, the mechanism of inhibiting the senescence process in hypoxia in stem cells is still remain unknown. Keywords: human-Adipose derived Mesenchymal Stem Cell Cultures (h-AMSCs), Hypoxic Preconditioning, Senescence cell, Oct-4.